APLIKASI DUKUNGAN PELAJAR PANDEMI COVID JAKARTA - Nugroho, Adi Putro (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
The Corona virus has now infected more than 100 countries in the world. WHO has also declared theCorona virus a pandemic. This means that the Corona virus has spread to almost the entire world,including Indonesia. The virus is spread through human interaction from an infected person to anotherthrough droplets from the nose or mouth when the infected person coughs, sneezes and even exhales.This condition made the Indonesian government immediately make a decision to break the chain of thespread of COVID-19 by carrying out activities from home including learning system activities in a networkor called online as an effort to prevent transmission of the Corona Virus. From the impact of the Covidpandemic, it has a very bad impact on underprivileged students, because there are still many studentswho do not have facilities for online learning or e-learning. Therefore, the author intends to providesupport for students facing the Covid 19 pandemic in facilitating the rental of gadget and laptopequipment as well as individual and collective internet packages for Citizen Homes (RW) at affordableprices and open acceptance of donations gadget or laptop for people who want to help students throughbased applications. web with the Codeigniter framework, namely "NRS" which will be described in thisreport with the title "MANAGEMENT INFORMATION SYSTEM FOR PANDEMI COVID STUDENT SUPPORTWEB-BASED" which later students can access the web through the browser and the data. will be stored inthe mysql database